Perencanaan Peserta Didik di Yayasan Al-Qur’an Ibnu Jauzi Dramaga - Laudza Zulfa Nur Dipa; Endin Mujahidin; Nesia Andriana; Ahmad Sastra; Ulil Amri Syafri (Journal Of Administration and Educational Management (ALIGNMENT), 2025)
This study aims to analyze student planning at the Al-Qur'an Ibnu Jauzi Dramaga Foundation, including aspects of recruitment, selection, orientation, and placement of students. The research method used is qualitative research with a library and field research approach. Data collection techniques include observation, structured interviews, and documentation, which are analyzed through data triangulation to test the validity of the information. The results of the study indicate that student planning is carried out systematically, starting with an analysis of the capacity and needs for facilities and infrastructure. The recruitment process is carried out through the formation of a committee and direct promotion, selection is carried out through interviews and document verification, and orientation is carried out in the form of "Taaruf Kepondokaan" activities to introduce the environment and values ​​of the institution. Placement of students is based on gender and class level similarities, with a focus on Islamic learning materials. This study provides a concrete picture of student planning management in Islamic boarding school-based educational institutions.  Keywords: Student Planning, Recruitment, Selection, Orientation, Placement